Simulation of composition changes in reservoirs with large hydrocarbon columns and temperature gradient - Yashin Anton V.; Indrupskiy Ilya M.; Lobanova Olga A. (Общество с ограниченной ответственностью «Георесурсы», 2018)
This paper compares three methods for calculation of initial composition variation with depth in hydrocarbon reservoirs: considering thermal diffusion, considering temperature gradient without thermal diffusion effects; and by gravity forces only. Newton method-based numerical algorithm was implemented for solution of thermodynamic equations to evaluate pressure and hydrocarbon composition. Test calculations are performed for main gas-condensate reservoir of Vuktylskoye field with a gas column of 1350 m. The results obtained with the numerical algorithm indicate that gravity segregation impact is the strongest for all the cases considered. concentration decreases with depth for low molecular weight components and increases for high molecular weight components. The higher molecular weight of the component, the stronger variation of its concentration with depth. Initial reservoir pressure also changes accordingly. However, thermal diffusion also has a significant influence on variation of hydrocarbon composition with depth and initial reservoir pressure. For the test case considered, thermal diffusion magnifies the impact of gravity and results in strongly nonlinear dependencies of component concentrations on depth. When thermal gradient is taken into account without thermal diffusion effects, the results are only slightly different from those with the isothermal gravity segregation calculations. None of the calculation methods were successful in matching estimates of initial composition variation with depth obtained from well exploitation data. Physical mechanisms governing variation of composition within the main reservoir of the Vuktylskoye field require additional investigation. Despite the long history of the reservoir development, this problem was previously studied based only on field development data.
Keywords: hydrocarbon mixture; geothermal gradient; thermal diffusion; component composition; initial composition; gas condensate reservoir; Vuktylskoye field